Estimativas da taxa de cruzamento em progênies meio-irmãs de cajueiro anão precoce utilizando marcadores moleculares - Amaral, Nathália Dias de Oliveira (2010)
The cashew (Anacardium occidentale L.) is a perennial arboreal fruit tree that is currently cropped in several tropical countries around the World. This is a fruit of great importance to Brazil, as it is distinguished in the social and economic context for the high nutritional and commercial value of its products. Despite its importance, the cashew has shown several problems, showing a decrease in productivity of the orchards. Thus, breeding programs of cashew of Embrapa seek to broaden the genetic gain for traits of economic importance. But it is necessary to understand and evaluate the genetic basis available to enhance the selection of superior genotypes. The mating system is used in breeding programs because it allows better strategies to delineate sampling variability and to select suitable models to estimate the parameters of interest. The objective was to obtain information about the mating system of six families belonging to the cashew breeding program of Embrapa located in Pacajus – Ce, using microsatellite chewers. We sampled 24 open-pollinated progenies for each of the six families using six SSR markers (AOBR1, AOBR3, AOBR6, AOBR9 AOBR15 and AOBR18). Molecular markers revealed 16 alleles in all families surveyed, they ranged 2-3 alleles per locus, with an average of 2.66 alleles. The parameters of the outcrossing rates were estimated with the program MLTR for mixed mating model. In the families, estimates of multilocus outcrossing rate (tm) obtained by the EM method ranged from 0.193 (0.016) to 0.980 (0.017). The obtained estimates were tm for the population was 0.518 (0.133), the rate sited (tsmédio) was 0.464 (0.138), the outcrossing rate among relatives (tm - ts) was 0.054 (0.023) and the rate of inbreeding (s) was 0.482, these results show that the species is breeding mixed. With these results, we concluded that the cashew tree tends to outcrossing and that the outcrossing rate varies among families, a fact that should be taken into account in breeding programs and germplasm conservation.